AN EDUCATIONAL FRONTIER: HANNAH BREECE AND THE AMERICAN COLONIAL PROJECT IN ALASKA - Teggin, Edward Owen (Pengkajian Amerika, Universitas Gadjah Mada, 2025)
This article examines the role of Hannah Breece, a government schoolteacher in early 20th-century Alaska, as an agent of U.S. internal colonialism. Through an analysis of her experience in Alaska, this study explores how education functioned as a tool of assimilation, aiming to bring ‘modernity’ to indigenous and Russian-descended communities. Breece’s experiences illustrate the mechanisms of tailored migration, whereby specialized workers were deployed to the colonial frontier to reshape native societies through structured educational, religious, and legal interventions. While Breece was deeply committed to her mission, her reflections reveal tensions within the colonial project. She recognized the failures of the American education system in Alaska, and her accounts highlight the interplay between colonial education, missionary work, and governance. By centering on Breece’s account, this article situates her within the larger framework of U.S. expansionist policies while acknowledging her personal agency in carrying out, and at times questioning, their implications. Her story exemplifies the contradictions of colonial rule: the belief in progress through education, the erasure of indigenous cultural practices, and the unintended consequences of assimilationist policies. Through this case study, the article contributes to the broader discourse on American internal colonialism, demonstrating how individuals like Breece navigated the space between personal conviction and state-imposed transformation.